Prasasti Kawali dalam Pembelajaran IPS: Integrasi Nilai Historis dan Kultural - Rahayu, Ratih; Warto; Akhmad Arif Musadad (LPPM Universitas Terbuka, 2025)
The Kawali Inscription, discovered in Ciamis Regency, West Java, is a significant historical artifact dating back to the 5th century AD. As one of the few surviving sources from the Sunda Kingdom, it offers valuable insights into the region's political, cultural, and historical context. This study aims to explore the historical and cultural values embedded in the inscription and examine how these can be effectively integrated into the Social Studies (IPS) curriculum for elementary and secondary education. Employing a qualitative approach with historical and content analysis methods, the research reveals that the Kawali Inscription is a rich resource for fostering students’ understanding of local history, strengthening cultural identity, and promoting critical thinking. The integration model includes the development of contextual learning materials, interactive teaching strategies, and project-based assessments aligned with curriculum objectives. This approach not only enriches historical learning but also supports character education through appreciation of Indonesia’s cultural heritage.